A performance management model for supporting improved local government service delivery : a case study of the Joe Gqabi District Municipality - Ndevu, Zwelinzima Julian (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.